Effect of flaxseed oil double emulsion with tea polyphenol on the gel characteristics, antioxidant property and water mobility in reduced‐fat pork batter - Li, Yan‐ping; Bai, Rong; Feng, Liang; Kang, Zhuang‐Li; Xu, Gui‐hua; Ma, Han‐Jun (International journal of food science & technology, 2022)
Summary The changes in gel characteristics, rheology and antioxidant properties, microstructure and water mobility were studied to investigate the potential use of flaxseed oil double emulsion to replace pork back‐fat (25%, 50%, 75% and 100%) in reduced‐fat pork batter. The flaxseed oil double emulsion (pH 6.0) was made of 20 mL 0.5% tea polyphenol solution (w/w), 20 mL flaxseed oil, 60 mL 4% whey protein (w/w) and 400 mL 2% Arabic gum solution. The result showed that the TBARS, L*, and a* values of pork batter significantly decreased (P < 0.05) when the flaxseed oil double emulsion replacing the pork back‐fat was ≤50%. Meanwhile, the pH, emulsification stability, hardness, springiness, gumminess, chewiness, cooking yield and G′ at 80 °C significantly increased (P < 0.05). In addition, the mobility of water in cooked batter first decreased and then increased (P < 0.05) with increasing flaxseed oil double emulsion. In addition, the microstructure of cooked pork batter with 50% flaxseed oil double emulsion has a continuous, tighter and regular structure, with the pores being smaller and more uniform. Overall, the replacement of pork back‐fat with flaxseed oil double emulsion at 50% reduced‐fat content could improve the quality of pork batter. Flaxseed oil double emulsion could replace of pork back‐fat to improved the quality of pork batter, led to the TBARS, L*, and a* values decreased when the flaxseed oil double emulsion ≤50%, and the pH, emulsification stability, cooking yield, and G′ at 80 °C increased.